Exploring Lifestyle Medicine in Rheumatic and Musculoskeletal Diseases: Findings From a Modified World Café Study - Megan Curran; Kevin Durkan; Stacey Grealis; Sean McKenna; Clodagh Toomey; Kate McCann; Norelee Kennedy; Audrey Tierney (Lifestyle Medicine, 2026)
ABSTRACT Introduction Although lifestyle medicine plays a recognised role in rheumatic and musculoskeletal disease (RMD) management, understanding how it is experienced is essential for developing effective lifestyle interventions. This study aimed to explore experiences and the impact of lifestyle medicine in RMD care and identify key facilitators and barriers to its implementation into RMD care from the perspectives of people living with an RMD and those involved in RMD care. Methodology A qualitative descriptive approach was used, employing a modified World Café methodology, informed by Public and Patient Involvement. Participants were purposively and snowball sampled, including adults living with RMDs, carers, family members, healthcare professionals (HCPs) and researchers. Data were analysed using Braun and Clarke's reflexive thematic analysis. Results Seventeen participants took part. Four main themes emerged: (1) the importance of social connection; (2) the role of HCPs in facilitating lifestyle changes; (3) the significance of lifestyle medicine self‐management; and (4) factors impacting lifestyle medicine management. Subthemes highlighted the value of peer support, access to reliable information, healthcare resource shortages and the potential of group consultations in RMD care. Conclusion These findings highlight key areas for addressing lifestyle medicine in RMD care and support the co‐development of lifestyle interventions, including group consultations, for future feasibility and acceptability evaluation.